Bank risk management in developing economies : addressing the unique challenges of domestic banks - Onyiriuba, Leonard O. (Academic Press, 2016)
Bank Risk Management in Developing Economies: Addressing the Unique Challenges of Domestic Banks provides an up-to-date resource on how domestically-based banks in emerging economies can provide financial services for all economic sectors while also contributing to national economic development policies. Because these types of bank are often exposed to risky sectors, they are usually set apart from foreign subsidiaries, and thus need risk models that foreign-based banks do not address. This book is the first to identify these needs, proposing solutions through the use of case studies and analyses that illustrate how developing economic banking crises are often rooted in managing composite risks. The book represents a departure from classical literature that focuses on assets, liabilities, and balance sheet management, by which developing economy banks, like their counterparts elsewhere, have not fared well. - Resumé vydavatel
Keywords: bankovnictví -- rozvojové země; rizikový management; banking -- developing countries; risk management; monografie; elektronické knihy; monographs; electronic books